Charakter narodowy Polakow i innych - Lewandowski, Edmund, 1946- (Londyn : Aneks ; Warszawa : Polityka, 1995)
A sociological treatment of the Polish national character and trait.
Includes bibliographical references.
Keywords: National characteristics, Polish